LGBT recognition in EU accession states: How identification with Europe enhances the transformative power of discourse. Issue 4 (14th January 2016) - Vasilev, George
Abstract: In the EU accession literature, there is a tendency to downplay the role of discourse in facilitating norm diffusion, particularly when domestic resistance towards European norms is strong. The assumptions in this thinking are that critical deliberations and civil society activism simply lack the potency required to elicit norm conforming behaviour in accession states and that the only realistic hope for achieving this rests with the introduction of material incentives that make the costs of normative adaptation lower than its rewards. I focus on developments in the field of LGBT politics to challenge these assumptions and to specify the conditions under which discursive strategies are likely to stimulate the domestic uptake of contentious norms. I highlight shared identity as a crucial factor in the success of discursive influence, contending that under conditions of identity convergence, a cultural environment prevails in which norm promoters can more effectively ignite a process of deliberative reflection, shame norm-violators into conformance and cultivate resonance around controversial ideas. I develop these arguments through an analysis of LGBT and accession politics in Croatia and Serbia, contending that Croatia's strong identification with Europe accelerated LGBT recognition there while Serbia's relatively weaker identification with Europe slowed it down.